HBsAg Frequency in Porters Applying to Public Health Laboratory - Harun Sozmen (GoAcademica Research & Publishing, 2020)
Hepatitis B virus infections are one of the major health problems of the world. Mainly parenterally transmitted HBV can be found in blood but less frequently in body fluids such as saliva, semen, sweat, and tears, and transmission may occur percutaneously. For this reason, it is important to investigate HBsAg in carrier screenings for public health. In this study, HBsAg frequency microparticle ELISA (Vitros 3600, Ortho-Clinical Diagnostics) in serum samples taken to the Ministry of Health Afyonkarahisar Public Health Laboratory for porter screening of sector employees such as food, cleaning and tourism between September 2011 and March 2012. It was researched by method. Samples with a positive reaction were verified by running the same kit a second time. Results and data were evaluated retrospectively. A total of 1961 porteurs, 311 (15.8%) women, aged between 18-65, were included in the study, 1096 of the porter was food (56.0%), 312 was tourism It was determined that he worked in the cleaning (4.0%) sector and 470 (24.0%) of them were new recruits. HBsAg positivity was found in 39 (1.9%) carriers, five of whom were women. It was determined that 32 (82.0%) of the HBsAg positive porter were working in the food sector, 4 (10.3%) were working in the cleaning sector, and 3 (7.7%) were new recruits. Most epidemiological studies on hepatitis B in our country show that intra-family or intra-community horizontal transmission of HBV in childhood and adolescence is at the forefront. In addition to parenteral applications, body fluids such as saliva, sweat and tears are also prominent in community horizontal transmission. For this reason, it is important to check HBsAg in carrier screenings in terms of public health.